2008
DOI: 10.1029/2008gl033817
|View full text |Cite
|
Sign up to set email alerts
|

Variable winds on Venus mapped in three dimensions

Abstract: [1] We present zonal and meridional wind measurements at three altitude levels within the cloud layers of Venus from cloud tracking using images taken with the VIRTIS instrument on board Venus Express. At low latitudes, zonal winds in the Southern hemisphere are nearly constant with latitude with westward velocities of 105 ms À1 at cloudtops (altitude $ 66 km) and 60-70 ms À1 at the cloud-base (altitude $ 47 km). At high latitudes, zonal wind speeds decrease linearly with latitude with no detectable vertical w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
133
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(156 citation statements)
references
References 16 publications
21
133
2
Order By: Relevance
“…For example Sánchez-Lavega et al (2008) found in Venus Express data that the zonal winds on Venus at the cloud level were approximately 60-100 m s −1 (the higher figure roughly at the tropopause level) from the equator out to about 5 50-60 • , and then decreased to the pole as is also seen here. They also found the peak meridional winds to be at 55 • S; this latitude is poleward of the Hadley cell on Earth.…”
supporting
confidence: 81%
“…For example Sánchez-Lavega et al (2008) found in Venus Express data that the zonal winds on Venus at the cloud level were approximately 60-100 m s −1 (the higher figure roughly at the tropopause level) from the equator out to about 5 50-60 • , and then decreased to the pole as is also seen here. They also found the peak meridional winds to be at 55 • S; this latitude is poleward of the Hadley cell on Earth.…”
supporting
confidence: 81%
“…The westward wind speeds found in the 1-μm region are 65-75 m/s. This is slower than the nominal Super-Rotation speed of 100 m/s usually found in the UV imaging of the cloud top at around 65-72 km (Kawabata et al 1980;Limaye and Suomi 1981;Belton et al 1991;Peralta et al 2007;Sanchez-Lavega et al 2008;Ignatiev et al 2009;Hueso et al 2015). Some of the above concluded that the slower wind speed comes from the lower altitude sampled by the 1-µm images than in the UV region.…”
Section: Introductionmentioning
confidence: 76%
“…However, the limited local time coverage in these observations may allow a significant contamination of the thermal tide component, which can be up to ∼10 m s −1 (Newman and Leovy, 1992). At lower heights (∼50 km), cloud tracking using near-infrared wavelengths suggests a much weaker circulation, which is below the detection limit of these measurements of a few m s −1 (Belton et al, 1991;Sánchez-Lavega et al, 2008). The adiabatic heating of the high latitude stratosphere above the cloud, which is suggested by the temperature increase at high latitude (Crisp, 1989;Pätzold et al, 2007), and the increased CO mixing ratio in the high-latitude below the cloud layer (Collard et al, 1993;Tsang et al, 2008) are thought to be attributed to the downward branch of the cloud-level Hadley circulation.…”
Section: Meridional Circulationmentioning
confidence: 96%